Sports experiences of elite athletes with intellectual disabilities and/or autism spectrum disorders - Duquesne, V.; Richard, R.; Andrieu, B.; Joncheray, H. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
Few sociological surveys have focused on the experiences of elite ath- letes with intellectual disabilities (ID) and/or autism spectrum disorders (ASD). However, more and more ID and/or ASD athletes are practicing elite sport. In this article, we seek to explore the mixed contacts of elite ID and/or ASD athletes with non-disabled people, resulting from their practicing both in sports contexts organized for disabled people (spe- cific context) and non-disabled people (mainstream context). Fifteen semi-structured interviews and eight days of ethnographic observa- tions were carried out with 7 elite table tennis players and 8 elite track- and-field athletes. The results analysis highlights the heterogeneity of the experiences - positive and negative - of elite ID and/or ASD athletes, both in specific and mainstream sports contexts. This heterogeneity of experiences invites favoring institutional arrangements that make the modalities of sport participation flexible for people with ID and/or ASD.